CONTEMPORARY CHALLENGES IN THE INTEGRATION OF ACCOUNTING AND AUDITING: STRATEGIC MECHANISMS FOR ENSURING FINANCIAL STATEMENT RELIABILITY (American Journal of Business Management, Economics and Banking, 2026)
The integration of accounting and auditing processes is fundamental to maintaining the integrity of global financial markets. However, the rapid digitalization of finance functions and the increasing complexity of regulatory frameworks have created significant friction between how accounting data is generated and how it is audited. This paper explores the contemporary challenges in harmonizing these two disciplines, emphasizing the technological asymmetry, data integration bottlenecks, and the persistent expectation gap. Utilizing the latest 2024–2025 statistical data from the Association of Certified Fraud Examiners (ACFE), the Public Company Accounting Oversight Board (PCAOB), and global Big Four surveys, this study highlights the urgent need for strategic mechanisms to ensure financial statement reliability. The findings suggest that transitioning from traditional retrospective auditing to continuous assurance models, powered by Artificial Intelligence (AI) and blockchain technology, can significantly mitigate the risk of financial misstatements and reduce audit deficiency rates.